Array - Yulianingsih, Ririn Dwi; Pujosusanto, Ari (LATERNE, 2023)
Speaking skills are activities these involve the skill of producing information conveyed through a sequence of words as an expression to express a message or idea in the form of oral sound and articulation in accordance with the needs of the listener or interlocutor. It is known that the average speaking score of students in class XI - IBB at SMA Negeri 2 Sidoarjo through daily tests was in the low category. So an effective media is needed to help improve students’ speaking skills by using mobile phone media "Lingbe". "Lingbe" is a community-based application in which there are many users from all parts of the country who have the same goal of learning foreign languages and looking for partners to practice their language. The purpose of this research is to find out how effective "Lingbe" is on improving speaking skills in German. The research method used was quantitative Pre Experimental Design with One Group Pre-test Post-test design. The sample used was all students of class XI - IBB at SMA Negeri 2 Sidoarjo totaling 33 students. The results of the SPSS-assisted N-Gain test calculating the pre-test and post-test scores showed a score of 0.55 with a percentage of 56% which stated that the media used was quite effective. The results of hypothesis testing with the SPSS-assisted t-test showed a significant value of 0.000032479 with a significance level of 5% (0.05) which states that the null hypothesis (H0) is rejected and accepts hypothesis one (H1) which states that the mobile phone application media "Lingbe" is effective for improving students’ speaking skills. The conclusion based on this research shows that the mobile application media "Linbge" is effective as an improvement in German speaking skills of students of class XI - IBB SMAN 2 Sidoarjo.